ANALISIS PUBLISITAS @SARI.ORGANIK MELALUI MEDIA SOSIAL INSTAGRAM - Dewi Septika; Mariana Rista Ananda Siregar; Ratih Siti Aminah (UNIVERSITAS PAKUAN, 2021)
This research was conducted in order to identify Sari Organik publicity analysis through Instagram social media based on the Iriantara concept which consists of the basic principles of publicity. This type of research is descriptive qualitative, this research focuses on one of the activities in Sari Organik, namely publicity activities on Instagram social media. In this regard, this qualitative descriptive approach is expected to explain the situation, problems and @sari.organik publicity activities through social media. This research was conducted at Sari Organik in February 2020. Data analysis techniques used were data reduction, data presentation, and conclusions, so that the data collected was only important data because it had been sorted. This study uses observation techniques, in-depth interviews, and documentation, meaning researchers get data from these 3 techniques. The results showed that the publicity activities at Sari Organik which were carried out using the basic principles of publicity from the Iriantara concept were very effective with wide and inexpensive reach. Publication activities are very important to support activities in selling products. As for the focus of the media used as publicity media is Instagram social media. Instagram is one of the media that is loved today as well as Sari Organic using Instagram as a media publicity.